Real-time PCR detection of mixed Plasmodium ovale curtisi and wallikeri infections in human and mosquito hosts. - Varun R Potlapalli; Meredith S Muller; Billy Ngasala; Innocent Mbulli Ali; Yu Bin Na; Danielle R Williams; Oksana Kharabora; Srijana Chhetri; Mei S Liu; Kelly Carey-Ewend; Feng-Chang Lin; Derrick Mathias; et al. (PLoS Neglected Tropical Diseases, 2023)
Plasmodium ovale curtisi (Poc) and Plasmodium ovale wallikeri (Pow) represent distinct non-recombining Plasmodium species that are increasing in prevalence in sub-Saharan Africa. Though they circulate sympatrically, co-infection within human and mosquito hosts has rarely been described. Separate 18S rRNA real-time PCR assays that detect Poc and Pow were modified to allow species determination in parallel under identical cycling conditions. The lower limit of detection was 0.6 plasmid copies/μL (95% CI 0.4-1.6) for Poc and 4.5 plasmid copies/μL (95% CI 2.7-18) for Pow, or 0.1 and 0.8 parasites/μL, respectively, assuming 6 copies of 18s rRNA per genome. However, the assays showed cross-reactivity at concentrations greater than 103 plasmid copies/μL (roughly 200 parasites/μL). Mock mixtures were used to establish criteria for classifying mixed Poc/Pow infections that prevented false-positive detection while maintaining sensitive detection of the minority ovale species down to 100 copies/μL (<1 parasite/μL). When the modified real-time PCR assays were applied to field-collected blood samples from Tanzania and Cameroon, species identification by real-time PCR was concordant with nested PCR in 19 samples, but additionally detected two mixed Poc/Pow infections where nested PCR detected a single Po species. When real-time PCR was applied to oocyst-positive Anopheles midguts saved from mosquitoes fed on P. ovale-infected persons, mixed Poc/Pow infections were detected in 11/14 (79%). Based on these results, 8/9 P. ovale carriers transmitted both P. ovale species to mosquitoes, though both Po species could only be detected in the blood of two carriers. The described real-time PCR approach can be used to identify the natural occurrence of mixed Poc/Pow infections in human and mosquito hosts and reveals that such co-infections and co-transmission are likely more common than appreciated.